Mortality among individuals with chronic kidney disease based on the 2012 and 2021 KDIGO blood pressure targets - Sijue Zou; Yan Zhang; Xin He; Jiawei Cheng; Songkai Wang; Yiwei Xiong; Zhangzhe Peng; Xiang Ao; Qiongjing Yuan (Scientific Reports)
Abstract The 2021 Kidney Disease: Improving Global Prognosis (KDIGO) guidelines set a target systolic blood pressure (SBP) of 120 mmHg for chronic kidney disease (CKD) patients. This paper aims to compare mortality outcomes in CKD patients following the 2021 KDIGO guidelines versus the 2012 KDIGO guidelines. We used the National Health and Nutrition Examination Survey (NHANES) database to categorize CKD patients into four groups: “above 2021 KDIGO only”, “above 2012 KDIGO only”, “above both targets” and “controlled with both targets”. We compared differences in all-cause and cardiovascular deaths among these groups. In total, 10,612 CKD patients from the 2001–2018 NHANES database were identified. Subsequently, 2,226 patients lacking mortality information and 1,157 without crucial laboratory data were excluded. 7,229 CKD patients were enrolled, with 50.67% above both targets, 27.1% controlled within both targets, 1.01% above the 2012 KDIGO target, and 21.22% only above the 2021 KDIGO target. In multivariate analyses, the risk of all-cause mortality was not statistically significant (hazard ratio (HR): 0.91, 95% confidence interval (CI): 0.8–1.02, P = 0.11) for patients above the 2021 KDIGO target only compared to those controlled with both targets. Similar results were found for cardiovascular deaths. The 2021 KDIGO guidelines did not differentiate high-risk CKD populations in terms of all-cause death and cardiovascular death, compared with the 2012 KDIGO guidelines.